2014
DOI: 10.1021/es500563q
|View full text |Cite
|
Sign up to set email alerts
|

Americium(III) Capture Using Phosphonic Acid-Functionalized Silicas with Different Mesoporous Morphologies: Adsorption Behavior Study and Mechanism Investigation by EXAFS/XPS

Abstract: Efficient capture of highly toxic radionuclides with long half-lives such as Americium-241 is crucial to prevent radionuclides from diffusing into the biosphere. To reach this purpose, three different types of mesoporous silicas functionalized with phosphonic acid ligands (SBA-POH, MCM-POH, and BPMO-POH) were synthesized via a facile procedure. The structure, surface chemistry, and micromorphology of the materials were fully characterized by (31)P/(13)C/(29)Si MAS NMR, XPS, and XRD analysis. Efficient adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 45 publications
4
31
0
1
Order By: Relevance
“…Generally,amaterial is considered as an excellent adsorbent if K d is over 10 4 mL g À1 .P articularly, K d Eu was up to 1.73 10 5 mL g À1 (99.43 %r emoval rate) at pH 2.6. Such high K d indicate that 1 has obviously higher affinity toward Eu 3+ than reported silica-phosphonic acid, [28] activated carbon [27] and ZSM-5 zeolite [13] (Supporting Information, Table S8).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Generally,amaterial is considered as an excellent adsorbent if K d is over 10 4 mL g À1 .P articularly, K d Eu was up to 1.73 10 5 mL g À1 (99.43 %r emoval rate) at pH 2.6. Such high K d indicate that 1 has obviously higher affinity toward Eu 3+ than reported silica-phosphonic acid, [28] activated carbon [27] and ZSM-5 zeolite [13] (Supporting Information, Table S8).…”
Section: Resultsmentioning
confidence: 90%
“…[11] Thes trongly acidic high-level radioactive liquid wastes (HLLW) put forward higher request on the adsorbents for lanthanide ions. [4a] At present, many adsorbents for Eu 3+ removal, such as silica-phosphonic acid [28] and PUR foam @HTTA [29] are greatly limited because of low capacity or failure to adsorb Eu 3+ in acidic conditions.Itishighly needed to develop new adsorbents that could the efficiently recover lanthanide ions from the complex wastewater for radionuclide remediation. Therefore,t he Eu 3+ adsorption for 1 in acidic solutions was systematically studied.…”
Section: Resultsmentioning
confidence: 99%
“…Three types of phosphoric acid modified silica, SBA-POH, MCM-POH, and BPMO-POH, were employed for the sorption of Am(III) and Eu(III) [94]. The coordination number was obtained from EXAFS.…”
Section: Adsorption Mechanism Of Heavy Metalsmentioning
confidence: 99%
“…Due to the remarkable coordination ability to fission products, organophosphorus compounds like TBP [11], TRPO [12] and Cyanex 272 [13] have been widely used in the solvent extraction processes in nuclear industry [14]. In our previous research, we reported the functionalization of mesoporous silicas with organophosphorus ligands, including neutral alkyl phosphine oxide [15] and acidic phosphonic acid derivatives [16], for actinides adsorption. And the results showed that the adsorbents were promising for the efficient separation of radionuclides in nuclear fuel cycles.…”
Section: Introductionmentioning
confidence: 99%